Nicotine supplementation enhances simulated game performance of archery athletes. Issue 1 (18th February 2021) - Hung, Bao-Lien; Chen, Li-Jung; Chen, Yi-Ying; Ou, Jhih-Bang; Fang, Shih-Hua
Abstract: Background: Nicotine is beneficial to mood, arousal and cognition in humans. Due to the importance of cognitive functioning for archery athletes, we investigated the effects of nicotine supplementation on the cognitive abilities, heart rate variability (HRV), and sport performance of professional archers. Methods: Eleven college archers were recruited and given 2 mg of nicotine supplementation (NIC group) and placebo (PLA group) in a crossover design. Results: The results showed that at 30 min after the intake of nicotine gum, the "correct rejection" time in the NIC group was significantly lower than that of the PLA group (7.29 ± 0.87 vs. 8.23 ± 0.98 msec, p < 0.05). In addition, the NIC group completed the grooved pegboard test in a shorter time than the PLA group (48.76 ± 3.18 vs. 53.41 ± 4.05 s, p < 0.05), whereas motor reaction times were not different between the two groups. Saliva α-amylase activity was significantly lower after nicotine supplementation ( p < 0.01) but increased immediately after the archery test in the NIC group ( p < 0.05). In addition, nicotine supplementation significantly decreased HRV and increased the archery score (290.58 ± 10.09 vs. 298.05 ± 8.56, p < 0.01). Conclusions: Nicotine enhances the performance of archery athletes by increasing cognitive function and stimulating the sympathetic adrenergic system.